Dynamics of Wolbachia on Malaysian Aedes albopictus with reference to dengue virus / Sylvia Joanne Laurence - Sylvia Joanne, Laurence (2016)
Dengue virus belonging to the family Flaviviridae is currently the major vector borne arboviral disease in the tropics. The virus is transmitted by Aedes mosquitoes. Both the primary vector Aedes aegypti and the secondary vector Aedes albopictus are capable of transmitting all four dengue virus serotypes. Vector control has been the hallmark for the surveillance and control of dengue. Wolbachia pipientis are vertically transmitted intracellular gram negative bacteria that have been associated with their capabilities to alter their host reproductive phenotypes. Wolbachia-based strategies have been proposed for control of vector population and pathogen transmission rate. Aedes albopictus is spreading at an alarming rate and may one day displace the population of Ae. aegypti in Malaysia as have been observed in a few other countries. In this study, the role of Wolbachia on Malaysian Ae. albopictus dynamics and on its susceptibility towards dengue virus have been elucidated. Wolbachia infection status was studied and was found that most (91.6%) of Malaysian Ae. albopictus tested were superinfected with wAlbA and wAlbB which each fell into two distinct clades. Wolbachia was found in all gonads and in some midguts of the mosquitoes. Colonies of naturally Wolbachia infected Ae. albopictus and antibiotic treated Wolbachia free Ae. albopictus was generated. Removal of Wolbachia from Malaysian Ae. albopictus caused reduction in their fecundity, longevity and egg viability. Unidirectional cytoplasmic incompatibility was expressed which could be used for Wolbachia-based Ae. albopictus population control strategies in the future. Wolbachia did not affect Malaysian Ae. albopictus dengue infection and dissemination rate on all four dengue virus serotypes. In addition, Malaysian Ae. albopictus was shown to be a better vector for dengue serotype one (DENV-1) compared to the rest.